Animal health law - Lipińska, Izabela (Przegląd Prawa Rolnego, 2019)
The subject of the article is the issues related to the implementation of EU legal solutions concerning the protection of the health of farm animals, while the purpose of the considerations is to evaluate the legal regulation adopted to implement the package of measures aimed at animal health that have been in place since 2013, and propose the direction of necessary changes in the national legislation in this area. The new animal health legislation entails the amendment or repeal of a number of national provisions on animal disease control, in particular those which were transpositions of directives and EU decisions now repealed. The legal instruments provided for in the regulation are expected to contribute to the achievement of a fully integrated internal market and to prevent the spread of infectious diseases, provided that the existing animal health status is maintained as far as possible.